Factors related to the clothing preferences for school of selected female students of the U.P. College of Home Economics, Diliman Quezon City gnes Francesca S. Bacaltos ; Ma. Monica R. Escano, adviser. - Bacaltos, Agnes Francesca S.; Escano, Ma. Monica R. (2010.)
ABSTRACT This is a descriptive study conducted to determine the factors that relate to selected female students' clothing preference for school. This study determined the types of clothing frequently worn by the respondents and the relation of the degree program, group organization, and modes of transportation with the clothing preference for school of the selected respondents. This study hoped to provide clothing manufacturers and merchandisers a brief portion of the teenage population's clothing preferences which will help in planning their future back-to-school collections. The research also gives future students who plan to research regarding clothing preferences, a point of comparison and reference for their future study. The objectives of the study were achieve through the survey method. Using a questionnaire distributed among 100 (20 from each of the 5 departments in the College, 5 from each academic year level) purposively selected female students from the College of Home Economics in UP Diliman. The tallied data were presented and analyzed with the use of frequency distribution and percentages. Results of the survey suggest that the clothing preferences for school among the respondents may be affected by the degree program and their mode of transportation since most of the respondents favor clothing that are comfortable. The clothing most commonly worn by the respondents are the t-shirt and pants.The study revealed that the factors which commonly influence the students' clothing preference the most are celebrities and icons. Fashion blogs and online ads also play an important role in the clothing choices of the selected respondents. For future studies, it is best that the researcher conduct a comparative study among different colleges or among different universities. Through this garment manufacturers and merchandisers will have an insight on the clothing preferences of female college students and will help in planning their future back-to-school collections.
Thesis (B.S. Clothing Technology)--University of the Philippines Diliman.
Keywords: College students -- Clothing; Clothing and dress -- Psychological aspects